Peripherally Inserted Central Venous Catheter (PICC) Line Use for Conjoined Twins: Single-Center Experience - Mohamed Elzahrani; Yousof Al Zahrani; Alwaleed Alqarni; Meshal Alothri; Mohammed Al Moaiqel; Mohammed Alotaibi; Amin Alzahrani; Abdulaziz Almulhim (The Arab Journal of Interventional Radiology)
Purpose This article assesses the feasibility, safety, and efficacy of peripherally inserted central catheters (PICCs) in conjoined twins.